Contos de enigma: estratégias pragmáticas de processamento textual - Gonçalves, Grace de Castro (2007)
The purpose of this work is researching the pragmatic strategies of the textual processing, based on the line of research of Reading, Writing and Teaching Portuguese Language. As elementary and high school teachers, we observe that our students depend on us to read, because they unknow or they are not conscious about such strategies. So, we must increase our knowledge about this subject, intending to prospect opportunities for Portuguese Language teachers can develop activities to raise the independent reader. We chose, as corpus, the enigma narratives Caio Fernando de Abreu s O Inimigo Secreto, Coelho Neto s A Sombra and Luís Martins s Os idos de Março. These narratives were chosen based on the fact that chalenging texts are showed as ludic games and make easier the teaching and learning of reading strategies. In order to develop this investigation, we created subsided by theoretician of Textual Linguistic and Theory of the Discourse Processing the following research questions: which textual process strategies do orient the reader to construct the senses and how can such strategies contribute to the development of independent readers at classroom? The specific intent is to verify what are these strategies and how they can contribute to the reader independency. That analysis allowed to identify frames, reference and referencial progress as strategies to orient the sense construction and to conclude that promoting the identification and application of such strategies at classroom contributes to the development of independent readers